Functional and genetic analysis in type 2 diabetes of Liver X receptor alleles - a cohort study - Gustafsson Jan-Åke; Brismar Kerstin; Östenson Claes G; Efendic Suad; Lecoeur Cecile; Gu Harvest F; Nilsson Maria; Dahlman Ingrid; Froguel Philippe; Vaxillaire Martine; Dahlman-Wright Karin; Steffensen Knut R (BMC, 2009)
Abstract Background Liver X receptor alpha (LXRA) and beta (LXRB) regulate glucose and lipid homeostasis in model systems but their importance in human physiology is poorly understood. This project aimed to determine whether common genetic variations in LXRA and LXRB associate with type 2 diabetes (T2D) and quantitative measures of glucose homeostasis, and, if so, reveal the underlying mechanisms. Methods Eight common single nucleotide polymorphisms in LXRA and LXRB were analyzed for association with T2D in one French cohort (N = 988 cases and 941 controls), and for association with quantitative measures reflecting glucose homeostasis in two non-diabetic population-based samples comprising N = 697 and N = 1344 adults. Investigated quantitative phenotypes included fasting plasma glucose, serum insulin, and HOMAIR as measure of overall insulin resistance. An oral glucose tolerance test was performed in N = 1344 of adults. The two alleles of the proximal LXRB promoter, differing only at the SNP rs17373080, were cloned into reporter vectors and transiently transfected, whereupon allele-specific luciferase activity was measured. rs17373080 overlapped, according to in silico analysis, with a binding site for Nuclear factor 1 (NF1). Promoter alleles were tested for interaction with NF1 using direct DNA binding and transactivation assays. Results Genotypes at two LXRB promoter SNPs, rs35463555 and rs17373080, associated nominally with T2D (P values 0.047 and 0.026). No LXRA or LXRB SNP associated with quantitative measures reflecting glucose homeostasis. The rs17373080 C allele displayed higher basal transcription activity (P value < 0.05). The DNA-mobility shift assay indicated that oligonucleotides corresponding to either rs17373080 allele bound NF1 transcription factors in whole cell extracts to the same extent. Different NF1 family members showed different capacity to transactivate the LXRB gene promoter, but there was no difference between promoter alleles in NF1 induced transactivation activity. Conclusion Variations in the LXRB gene promoter may be part of the aetiology of T2D. However, the association between LXRB rs35463555 and rs17373080, and T2D are preliminary and needs to be investigated in additional larger cohorts. Common genetic variation in LXRA is unlikely to affect the risk of developing T2D or quantitative phenotypes related to glucose homeostasis.